2020
DOI: 10.21071/az.v69i267.5351
|View full text |Cite
|
Sign up to set email alerts
|

Cinética de degradación ruminal in situ de ensilado de rastrojo de maíz (Zea mays) con niveles crecientes de urea

Abstract: Se estudió el efecto de la inclusión de urea sobre la composición y cinética de degradación ruminal in situ en el ensilado de rastrojo de maíz. Se partió de cuatro de tratamientos al adicionar el 0, 1, 2 y 3% de urea a una mezcla de rastrojo de maíz con el 10% de melaza. Se elaboraron 128 microsilos (3 kg/unidad y 4 repeticiones por tratamiento). La apertura de los silos se realizó a los 7, 14, 21, 28, 35, 42, 49 y 56 días. Se determinó el contenido de la materia seca (MS), materia orgánica (MO), proteína brut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
0
0
1
Order By: Relevance
“…Hemicellulose was found by difference across (4). (4) With elemental analysis, the content of C, H, N, and S, was determined following the regulations described in the BS EN 15104:2011 18 standard. In the proximal analysis, the amount of volatile material, ash, and fixed carbon was determined, as indicated in the BS EN 15148:2009 19 and BS EN 14775:2009 20 standards.…”
Section: Physical-chemical Characterization Of the Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Hemicellulose was found by difference across (4). (4) With elemental analysis, the content of C, H, N, and S, was determined following the regulations described in the BS EN 15104:2011 18 standard. In the proximal analysis, the amount of volatile material, ash, and fixed carbon was determined, as indicated in the BS EN 15148:2009 19 and BS EN 14775:2009 20 standards.…”
Section: Physical-chemical Characterization Of the Samplementioning
confidence: 99%
“…Corn stover is abundant lignocellulosic biomass in Ecuador, generated as crop residue in one of the most important agricultural items in the country. Had been reported that 53% of producers in the region use it to feed their livestock, 27% use it for top dressing, leaving it on the ground, and the remaining 20% are burned 4 . This residue contains 35% cellulose, 20% hemicellulose, and 12% lignin 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Consecutivamente, la absorción posruminal que se genera a partir del alimento no fermentado por medio de una segunda masticación (Ireijo Mitsuta, 2020) cuyo producto desemboca en el abomaso -siendo este su estómago glandular dotado de enzimas como pepsina y ácido clorhídrico (Hristov et al, 2019)-facilita la absorción de nutrientes de forma proporcional al porcentaje de materia seca consumido, de tal manera que la urea transportada al torrente sanguíneo será excretada por medio de la orina; sin embargo, un porcentaje de esta y del amoniaco es reciclado por la microbiota ubicada en el rumen (Sánchez et al, 2020) como un sistema imperativo de reciclaje proteico por parte del animal (Viamonte Garcés et al, 2017).…”
Section: Importancia De La Fbn En Pasturas Y Sus Efectos En La Produc...unclassified